Upaya Room Supervisor Dalam Meningkatkan Kualitas Kamar Deluxe Pada Padma Resort Legian Kuta Bali - I Putu Ariska Mahendra; I Made Bayu Wisnawa; Ni Putu Yunik Anggreni (Universitas Triatma Mulya, 2025)
The purpose of this study was to determine the Room supervisor procedures in improving the quality of Deluxe rooms at Padma Resort Legian, Kuta Bali, knowing the obstacles faced by Room Supervisors in improving the quality of Deluxe rooms at Padma Resort Legian, Kuta Bali and efforts made in dealing with the obstacles experienced by Room Supervisors in improving the quality of Deluxe rooms at Padma Resort Legian, Kuta Bali. Data collection techniques are carried out by means of observation, interviews, and documentation. The results showed that there are several ways done by supervisors to improve room quality, namely communicating with housekeeping by giving morning briefing every day or by directly providing information to housekeeping such as a change in room status. The division of schedules that are irregular or change due to the limited number of employees. 2. Difficulty in fostering the discipline of the housekeepers due to some housekeepers relaxing during working hours.3. There is no indifferent response from some housekeepers in seeing something odd or seeing damage in the room. Efforts made to resolve obstacles are giving trust to those who get the assignment fi public area because they already have more abilities and skills than others, giving appreciation for a success or achievement that has been achieved by the housekeeper, training the housekeeper, and giving direction or notification to the housekeeper in anticipating all possibilities that can occur.